STATUS KUALITAS PERAIRAN WADUK SEI BALOI - BATAM DAN KELAYAKANNYA UNTUK BAHAN BAKU AIR MINUM - Soetrisno, Yudhi (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2006)
Sei Baloi is a reservoir in the Batam Industrial Development Area (BIDA),which developed especially for source of drinking water. This research wasconducted to know the water quality of Sei Baloi, and the suitability for thesource of drinking water. This research revealed that the water of Sei Baloi cannot directly used for drinking water due to concentrations of detergent, Cr, Cdand Pb were higher than the national standard for drinking water. Base on thisresult, it was suggested that the water of Sei Baloi need threatment forderease the above parameters.